An updated biosystematic approach to the leiosaurid genus Pristidactylus - Cei, José Miguel Alfredo María (2004)
A general discussion of the intra- and intergeneric biological relationships of the leiosaurid genus Pristidactylus has been carried out. Its cis-trans cordilleran species groups are reported and compared, also in agreement with results of the very recent molecular and morphological research by Frost et al. (2001). The new family Leiosauridae, including Enyalius, Diplolaemus, Leiosaurus and Pristidactylus, is taken into account, and ancient evolutionary relationships of the last named genus are considered. Present specific characters of Chilean, but mainly of Argentinian Pristidactylus taxa, are analyzed and compared. They are likely adaptive features from ancestral times of their common preglacial origin. Critical comments on the now postulated primitive position of the terrestrial forms instead of the formerly accepted arboreal forms as plesiomorphic evolutionary stage are presented as well.